Industry and production of the city of Jizzakh during the years of independence (Eurasian Journal of History, Geography and Economics, 2022)
This article provides information about the economy of the Jizzakh region, the transition from a centrally planned administrative-command mechanism to a free market economy, a radical reform of the economy of the Jizzakh region in order to form a socially oriented market economy